Identifying Barriers to Preemptive Kidney Transplantation in a Living Donor Transplant Cohort. Issue 4 (April 2018) - Helmick, Ryan A.; Jay, Colleen L.; Price, Brittany A.; Dean, Patrick G.; Stegall, Mark D.
Abstract : Background: Despite substantial evidence demonstrating clear benefit, rates of preemptive kidney transplantation (PreKTx) remain low in the United States. Our goal was to identify barriers to PreKTx. Methods: Using a telephone-administered questionnaire including questions about barriers, timing of referral, timing of education, we retrospectively studied first living donor kidney transplant recipients (2006-2010) at Mayo Clinic, Rochester, MN. Of 235 patients, 145 (62%) responded to the questionnaire (74 PreKTx and 71 non-PreKTx). We compared categorical data with Fisher exact test and median times with Wilcoxon rank sum test. Results: Polycystic kidney disease (PCKD), longer median time between diagnosis and transplant, and time between education about transplant and transplant correlated with PreKTx ( P < 0.01). The presence of at least 1 patient-identified barrier (lack of referral, financial barriers, medical barriers, no identified living donor and donor evaluation delays) was associated with non-PreKTx (0.034) though no single barrier predominated. Age, education level, insurance status and source of referral (primary care, nephrology, and nonphysician referral) were not associated with the rate of PreKTx. Univariate logistic regression identified white race, PCKD, and increased time from diagnosis as factors favoring PreKTx; PCKD and increased time remained significant factors after multivariate analysis. Conclusions: Even among a patient population that is primarily white, educated, and has a spouse or first-degree relative donor, PreKTx rates remain concerningly low. Increased time between diagnosis or education and transplant are predictors of PreKTx. Greater emphasis on transplant education earlier in the stages of chronic kidney disease and community outreach from transplant centers may help to increase the rate of PreKTx.